Asian and Axis resistance movements - Dupuy, Trevor Nevitt. 4 0 16; 5 (New York: : Watts, 1962)
The story of the resistance fighters in Asia and the Axis countries of Europe during World War II.
7.0;Young Adult;Young Adult.
Keywords: 2 -- 0; 6; World War, 1939-1945.;World War, 1939-1945.; 20; 2